MANUAL THERAPY FOR TREATING CHRONIC PELVIC PAIN SYNDROME - Frank, Sergii; Frank, Michael; Frank, George (World Science, 2020)
Chronic pelvic pain syndrome is a combination of multiple chronic urogenital pain syndromes. This paper deals with only some of them such as: prostate, bladder and vaginal pain syndromes as well as the possibility of treating non-infectious instances of the said syndromes with manual therapy. The study proves that manual therapy combined with shock wave therapy can successfully aid patients with treatment-resistant manifestations of chronic pelvic pain syndrome, in particular, prostatic, bladder and vaginal pain syndromes, who haven’t been able to achieve their desired results through conventional treatment.